2020
DOI: 10.1177/0284185120932391
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting cerebral blood flow specific to patients with diabetic retinopathy revealed by arterial spin labeling perfusion magnetic resonance imaging

Abstract: Background Previous neuroimaging studies have shown that patients with diabetic retinopathy (DR) were accompanied by abnormalities in cerebral functional and structural architecture, whereas the resting cerebral blood flow (CBF) alterations in patients with DR are not well understood. Purpose To explore CBF alterations in patients with DR using pseudo-continuous arterial spin labeling (pCASL) imaging. Material and Methods Thirty-one individuals with DR (15 men, 16 women; mean age = 53.38 ± 9.12 years) and 33 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…A total of 369 records were identified through database searching and citation searching, and Figure 1 shows the flowchart of literature search and study selection. We finally included 13 studies with 14 reports in the systematic review ( Last et al, 2007 ; Jor’dan et al, 2014 ; Novak et al, 2014 ; Rusinek et al, 2015 ; Xia et al, 2015 ; Jansen et al, 2016 ; Cui et al, 2017 ; Dai et al, 2017 ; Shen et al, 2017 ; Bangen et al, 2018 ; Zhang et al, 2019 ; Chau et al, 2020 ; Huang et al, 2021 ). One study performed analysis using both ROI and VBA methods ( Jansen et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 369 records were identified through database searching and citation searching, and Figure 1 shows the flowchart of literature search and study selection. We finally included 13 studies with 14 reports in the systematic review ( Last et al, 2007 ; Jor’dan et al, 2014 ; Novak et al, 2014 ; Rusinek et al, 2015 ; Xia et al, 2015 ; Jansen et al, 2016 ; Cui et al, 2017 ; Dai et al, 2017 ; Shen et al, 2017 ; Bangen et al, 2018 ; Zhang et al, 2019 ; Chau et al, 2020 ; Huang et al, 2021 ). One study performed analysis using both ROI and VBA methods ( Jansen et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study performed analysis using both ROI and VBA methods ( Jansen et al, 2016 ). As 1 of 8 VBA reports had no available coordinate ( Novak et al, 2014 ), 7 studies with 7 reports were finally included in the meta-analysis ( Xia et al, 2015 ; Jansen et al, 2016 ; Cui et al, 2017 ; Dai et al, 2017 ; Shen et al, 2017 ; Zhang et al, 2019 ; Huang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This elevation observed in diabetic retinopathy (DR) patients aligns with findings from previous studies. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 14 We also conducted this study on patients with DR, which revealed significantly higher CBF values in the left middle temporal gyrus and bilateral supplementary motor areas, as well as significantly lower CBF values in the bilateral calyces and bilateral caudate nuclei. 15 …”
Section: Introductionmentioning
confidence: 99%